BENTUK KEMITRAAN INDUSTRI DALAM PENGEMBANGAN KELAPA SAWIT DI DESA LOWONUA KECAMATAN BESULUTU KABUPATEN KONAWE - Yanti, Perni; Nikoyan, Anas; Arif, La Ode Kasno (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to ascertain the nature of industrial partnerships in palm oil development in Lawonua Village. The informants were selected using purposive and snowball sampling techniques, resulting in a total of 22 informants consisting of six farmer group administrators, six farmer group members, four local farmers, two migrant farmers, two village officials (the village head and the village secretary), and two company staff.  The data for this study was collected through a combination of documentation review and interviews with trained interview guides. The focal point of this study encompassed the various forms of industrial partnerships and the development of palm oil. The data analysis activities encompassed data reduction, data presentation, and conclusion drawing. The results of the study demonstrate that the core-plasma and general trade forms of partnership in palm oil development in Lawonua Village play a strategic role in strengthening farmers' access to land provision, production facilities, technical guidance, and market guarantees. The efficacy of palm oil development, as evidenced by the augmentation in productivity and effectiveness of palm oil farmers, has been demonstrated to be contingent upon the provision of inputs such as high-quality seeds and fertilizers, in conjunction with cultivation activities including planting, maintenance, and harvesting. The integration of the nucleus-plasma and general trading forms of partnership has resulted in a complementary collaboration model that supports the sustainability of palm oil farming.